PEMBERDAYAAN MASYARAKAT KELOMPOK USAHA MELALUI DIVERSIFIKASI IKAN TERI (Stolephorus Sp.) SEBAGAI STIK - Martini Djamhur; Mutmainnah Mutmainnah; Yuliana Yuliana; Rugaya Sero sero (Jurnal Abdi Insani, 2023)
ABSTRACT Sticks are processed fish products that are very popular with children and adults. This type of food is in the form of snacks consumed between main meals. Stick in the form of long flat thin slices made from wheat flour, tapioca flour, eggs, and water are fried and have a savory taste and crunchy texture. The fish ingredient added to the stick product to add nutritional value to the stick snack. Processed diversification can be business groups or independently to increase family income. Steak is a snack that tastes good and is easy to carry anywhere. The purpose of this activity can provide skills in making snacks that contain nutritional value to the community, especially for women who are members of the UMKM Mekar Jaya Tobter in the Ternate archipelago. And it can be used as additional family income if on a large scale. The resulting output targets are: Partners can process sticks from anchovies, partners in processing anchovies into partners increased skills, and can produce on a large scale. This activity was carried out in July 2022 with a demonstration. The demonstration activity process was exemplified to group members and involved in the activation process. The sticks made in this PKM activity come from anchovy caught by Bagan and are commonly found in Ternate city. These raw materials are needed on the market on a large scale. Increasing skills through this community service activity added value to group members.